the Encyclopedia of political thought - Sheldon, Garrett Ward, ed. 1954- (New Delhi: Viva Books Pvt. ltd., 2005)
"Encyclopedia of Political Thought is a resource for students or general readers who want to know more about the major ideas, philosophies, and concepts of civic administration that have influenced and shaped civilization past and present.".
"With particular emphasis on the 20th century, the encyclopedia contains more than 400 cross-referenced entries that make up an up-to-date survey of topics that have been crucial to the history of humankind, including the rise and fall of communism, the advent of feminism, and the advancement of democracy.".
"Key concepts and controversial issues are clearly defined and thoughtfully analyzed, with examples from current events used to enhance the reader's understanding of the ideas presented. Ideologies are not only considered within historical context but are also related to contemporary politics, enhancing the book's usefulness for reports, student debates, or general research. A chronology provides a linear presentation of the evolution of political thinking."--BOOK JACKET.
"Viva-Facts on File"
Includes bibliographical references and index.
Keywords: Political science -- Encyclopedias; Political science -- History -- Encyclopedias; World politics -- Encyclopedias